Iridoid glycoside dimers from fruits of Cornus officinalis and their anti-inflammatory activity - Shi, Ying-Chu; Yu, Yu-Xin; Gao, Jiu-Xia; Wang, Xin; Shang, Xiao-Ya; Xu, Jia (Frontiers in Chemistry, 2025)
A bioassay-guided phytochemical study of the fruits of Cornus officinalis led to the isolation of six new iridoid glycoside dimers, named corndiridoside A-F (1–6), along with 11 analogs (7–17). The structure of these dimers was elucidated using HRESIMS, 1D and 2D NMR, IR, and UV spectra, as well as literature comparisons. The anti-inflammatory activity of all compounds was evaluated, revealing a significant inhibitory effect on all dimers on the production of NO in LPS-stimulated RAW 264.7 cells at concentrations of 25 and 50 μM. Of the six, compounds 2 and 3 showed the strongest anti-inflammatory activity.